Evaluasi Sistem Informasi Manajemen Rumah Sakit (SIMRS) dengan Metode Hot-Fit pada Unit Rawat Jalan di Rumah Sakit PKU Muhammadiyah Kartasura - Enggar Pramudita Wijayanti; Asti Nurhayati (Lembaga Pengembangan Kinerja Dosen, 2024)
Hospital Management Information System (SIMRS) is a communication information technology system that can process and integrate all service process flows in the Hospital into a network that coordinates between divisions, both reporting and administrative procedures to be able to obtain precise and accurate information, and is part of a Health Information System. As an effort to improve the performance of the Hospital Management Information System (SIMRS), its implementation must be followed by an evaluation of the system itself to determine the positive aspects that encourage the use of the system and identify factors that cause obstacles. Evaluation is an important thing to do because it can produce negative findings from the use of a system. Evaluation covers various aspects of the use of information and communication technology in hospitals. The HOT-Fit method is one of the theoretical frameworks used to evaluate information systems in the field of health services. The HOT-Fit method also addresses the core components of information systems, namely Human, Organization, Technology and Net Benefit. The purpose of this study was to determine the evaluation of the Hospital Management Information System (SIMRS) with the HOT-Fit Method in the Outpatient Unit at PKU Muhammadiyah Kartasura Hospital. The research method used was quantitative research. The instrument used in this study was a questionnaire. The results of research on the evaluation of the Hospital Management Information System (SIMRS) with the HOT-Fit Method which shows positive and useful things in supporting health services to patients.